Combined ipilimumab and nivolumab first‐line and after BRAF‐targeted therapy in advanced melanoma. (2nd November 2019) - Mason, Robert; Dearden, Helen C.; Nguyen, Bella; Soon, Jennifer A.; Smith, Jessica Louise; Randhawa, Manreet; Mant, Andrew; Warburton, Lydai; Lo, Serigne; Meniawy, Tarek; Guminski, Alexander; Parente, Phillip; et al.
Abstract: The combination of ipilimumab and nivolumab is a highly active systemic therapy for metastatic melanoma but can cause significant toxicity. We explore the safety and efficacy of this treatment in routine clinical practice, particularly in the setting of serine/threonine‐protein kinase B‐Raf (BRAF)‐targeted therapy. Consecutive patients with unresectable stage IIIC/IV melanoma commenced on ipilimumab and nivolumab across 10 tertiary melanoma institutions in Australia were identified retrospectively. Data collected included demographics, response and survival outcomes. A total of 152 patients were included for analysis, 39% were treatment‐naïve and 22% failed first‐line BRAF/MEK inhibitors. Treatment‐related adverse events occurred in 67% of patients, grade 3–5 in 38%. The overall objective response rate was 41%, 57% in treatment‐naïve and 21% in BRAF/MEK failure patients. Median progression‐free survival was 4.0 months (95% CI, 3.0–6.0) in the whole cohort, 11.0 months (95% CI, 6.0‐NR) in treatment‐naïve and 2.0 months (95% CI, 1.4–4.6) in BRAF/MEK failure patients. The combination of ipilimumab and nivolumab can be used safely and effectively in a real‐world population. While first‐line efficacy appears comparable to trial populations, BRAF‐mutant patients failing prior BRAF/MEK inhibitors show less response.